Solution.
1) Subtract the first expression from the second expression and equate to the third
"\\frac{dx-dy}{x^2-y^2-yz-(x^2-y^2-zx)}=\\frac{dz}{z(x-y)}\\\\\n\\frac{d(x-y)}{x^2-y^2-yz-x^2+y^2+zx}=\\frac{dz}{z(x-y)}\\\\\n\\frac{d(x-y)}{z(x-y)}=\\frac{dz}{z(x-y)}\\\\\nd(x-y)=dz\\\\\n\\int d(x-y)=\\int dz\\\\\nz=x-y+C_1."
Then the first integral curves is
"z-x+y=C_1."
2) Add the first expression to the second and equate to the third
"\\frac{dx+dy}{x^2-y^2-yz+x^2-y^2-xz}=\\frac{dz}{z(x-y)}\\\\\n\\frac{d(x+y)}{2(x^2-y^2)-z(x+y)}=\\frac{dz}{z(x-y)}\\\\\n\\frac{d(x+y)}{2(x -y )(x+y)-z(x+y)}=\\frac{dz}{z(x-y)}\\\\"
Because
"x-y=z-C_1."
Then
"\\frac{d(x+y)}{2(z-c_1 )(x+y)-z(x+y)}=\\frac{dz}{z(z-c_1)}\\\\\n\\frac{d(x+y)}{(x+y)(2(z-c_1)-z)}=\\frac{dz}{z(z-c_1)}\\\\\n\\frac{d(x+y)}{(x+y)(z-2c_1)}=\\frac{dz}{z(z-c_1)}\\\\\n\\frac{d(x+y)}{(x+y)}=\\frac{(z-2c_1)dz}{z(z-c_1)}\\\\\n\\frac{d(x+y)}{(x+y)}=\\frac{2z-2c_1-z}{z(z-c_1)}dz\\\\\n\\frac{d(x+y)}{(x+y)}=\\left(\\frac{2}{z}-\\frac{1}{z-c_1}\\right)dz\\\\\n\\int\\frac{d(x+y)}{(x+y)}=\\int\\left(\\frac{2}{z}-\\frac{1}{z-c_1}\\right)dz\\\\\n\\ln|x+y|=2\\ln|z|-\\ln|z-c_1|+\\ln|c_2|\\\\\nx+y=\\frac{z^2 c_2}{z-c_1}"
Substitute the value "c_1"
"x+y=\\frac{z^2 c_2}{z-(z-x+y)}\\\\\nx+y=\\frac{z^2 c_2}{x-y}\\\\\nx^2-y^2=z^2 c_2"
Then the second integral curves is
"\\frac{x^2-y^2}{z^2}=c_2"
Comments
Leave a comment